DOES CEO POWERS MODERATE THE RELATIONSHIP BETWEEN INTELLECTUAL CAPITAL AND FINANCIAL DISTRESS? A COMPARATIVE STUDY - Muhammad, Naeem; Shoukat,Ali; Ahmad Shah,Durrani; Muzzammil,Siraj (International Journal of Business Reflections)
The purpose of this study is to investigate the impact of intellectual capital (IC) on financial distress (FD) as well as the moderating role of CEO Power (CEO_P) in Pakistan and India's comparative study. A quantitative approach is used in the study and secondary data is collected from financial reports of 110 firms registered at the Pakistan Stock Exchange (PSX) and also 110 firms at the Bombay Stock Exchange (BSX) from the study period 2016 to 2023. Panel data techniques are used for analysis. Both countries with stronger IC are less likely to face FD and CEO_P partially moderate this relationship IC_FD. Findings support this argument. Resource-based view (RBV) theory and managerial discretion theory (MDT) are used in this study. This study uses the modified value-added intellectual coefficient (MVAIC) method, which incorporates relational capital (RC) in measuring IC. This study investigates two economies with varying socioeconomic development and stresses the importance of IC in both countries in reducing the risk of FD. It also evaluates whether powerful CEOs use business resources for their benefit or not. This study has some implications for stakeholders, policymakers, and managers of business. These findings suggest that managers should prioritize IC to reduce the risk of default and accounting bodies should formulate strategies to reduce the powers of CEOs to protect the rights of stakeholders.